Search for A′→ μ+μ- decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; et al. (Physical review letters, 2019)
Searches are performed for both prompt-like and long-lived dark photons,A′,produced in proton-proton collisions at a center-of-mass energy of 13TeV. Thesesearches look forA′→μ+μ−decays using a data sample corresponding to anintegrated luminosity of 5.5fb−1collected with the LHCb detector. Neither searchfinds evidence for a signal, and 90% confidence-level exclusion limits are placedon theγ–A′kinetic-mixing strength. The prompt-likeA′search explores themass region from near the dimuon threshold up to 70GeV, and places the moststringent constraints to date on dark photons with 214< m(A′).740MeVand10.6< m(A′).30GeV. The search for long-livedA′→μ+μ−decays placesworld-leading constraints on low-mass dark photons with lifetimesO(1) ps.
Im Titel sind "+", "-" hochgestellt
Gesehen am 10.03.2021
R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. d’Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, H. Malygina, J. Marks, S. Neubert, A. Piucci, N. Skidmore, S. Stemmle, U. Uwer, A. Zhelezov [und weitere] (LHCb Collaboration)